(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Margaret Eleanor Atwood is an internationally acclaimed Canadian poet, critic and cultural activist. Even as a young girl, Atwood rejected to assume the role of stereotyped woman. She firmly shows her disregard for gender assumed roles. In her novels, she strictly opposes gender discrimination. Her novels explore the themes of victimisation and survival. Through her novels she speaks about subordination and oppressions of women in a patriarchal society. She clearly portrays how female bodies are exploited for the satisfaction of men’s sexual desires. All her women characters become aware of their individuality and finally reject the conventional gender role which is attributed to her. They all refuse to become a victim. They found out their lost part in them and finally achieve wholeness. This chapter focuses on the study of sexuality based on the select works of Margaret Atwood. This paper also focuses on how the female characters in her novels try to discover their own identities and humanity and how they recognise their complicity in the destructive world of power and victimisation. The novels taken for study are The Edible Women, Surfacing, Bodily Harm, The Handmaids Tale, and Cat’s Eye.